Chapter 6: From the ground up: Cultivating agriculture for nutrition [Nourishing Millions] - Yosef, Sivan (2016)
FEW SECTORS HAVE clearer links to nutrition than agriculture. Most simply, of course, agriculture is a source of food. Because many poor households around the world grow food that they both consume and sell for income, agricultural interventions can have a massive effect on the lives of people in developing countries. Through the decades, and most famously in Asia’s Green Revolution, development projects have sought to boost agricultural production of staple foods as a way of improving people’s nutrition. Yet, while consuming a sufficient quantity of calories is important, especially among undernourished populations, quality matters too. Thus, the traditional focus on producing enough food to meet people’s calorie needs has evolved into a deeper understanding that to improve nutrition, we also need people to consume balanced, high-quality, and diverse diets that contain enough essential nutrients to meet their daily requirements.